KEMAMPUAN GURU BIOLOGI DALAM MELAKSANAKAN PEMBELAJARAN SESUAI STANDAR OPERASIONAL PROSEDUR (SOP) LABORATORIUM PADA KOMPETENSI INTI KETRAMPILAN KELAS XI MIPA SEMSTER II TAHUN AJARAN 2019/2020 SMA NEGERI 2 KENDAL - MISTURIYAH MISTURIYAH (Universitas Pandanaran, 2021)
The purpose of this research is an effort to improve the Ability of Biology Teachers in Carrying Out Learning in Accordance with Laboratory Operational Procedures (SOP) in the Core Competencies of Class XI MIPA Class II Semester II SMA NEGERI 2 KENDAL in 2020. so that they are able to carry out practicum activities from preparation, implementation, evaluation. and follow-up of every practicum activity carried out. This type of research is Classroom Action Research (PTK). The main research subjects were students of class XI MIPA Semester II for the 2019/2020 academic year. The research location was in SMA 2. The number of actions carried out was 2 (two) times consisting of 2 cycles. Each cycle consists of 4 (four) stages which include planning, implementing, observing and reflecting. Kata Kunci : SOP Laboratorium, Praktikum, Nilai Siswa